Technical attributes of Australian youth soccer players: Implications for talent identification - Keller, B. S.; Raynor, A. J.; Bruce, L.; Iredale, F. (International Journal of Sports Science & Coaching, 2016)
Objectives: To determine whether the technical ability of Australian youth soccer players could distinguish between various playing levels. Design: A cross-sectional observational design was used with each player required to complete four technical tests. Methods: Sixty-two participants were representatives of three cohorts of youth soccer in Australia: national elite (n=18), state elite (n=22) and sub-elite (n=22). The technical tests used were Loughborough Short Passing Test (LSPT), long passing test (LPT), shooting test and speed dribbling, with all players familiarised with the tests prior to data collection. Differences between cohorts were analysed using a multiple analysis of variance test with follow-up analyses of variance and Tukey Honest Significant Difference post-hoc test, which were subsequently used to inform a sensitivity analysis, more specifically a bootstrapped receiver operating curve to determine cut-off scores for each variable. Results: The national elite cohort scored better than state- and sub-elite cohorts on the LSPT, however, the state elite produced the fastest time before penalties. The sub-elite cohort scored less points on the LPT compared to both national- and state-elite cohorts, on both feet. In regards to speed dribbling, national-elite players were faster than both the state- and sub-elite cohorts. Shooting accuracy and velocity were able to discriminate the national- and sub-elite cohorts on the dominant foot, with shooting velocity on the nondominant foot being faster for the national elite compared to both the state- and sub-elite cohorts. Conclusions: A number of differences in technical ability were identified between varying levels of Australian youth soccer players. Youth soccer coaches and sports scientists should use the cut-off scores for the technical tests in the talent identification and development process, with aspiring players aiming to reach these levels. ABSTRACT FROM AUTHOR